Altered hMSC functional characteristics in short-term culture and when placed in low oxygen environments: implications for cell retention at physiologic sites. (March 2014) - Bain, Owen; Detela, Giulia; Kim, Hae-Won; Mason, Chris; Mathur, Anthony; Wall, Ivan B
Background: It is very difficult to conserve critical cell characteristics during expansion in culture, particularly those of adult mesenchymal stromal cells (MSCs), whose characteristics can change rapidly even within a short period of expansion.Aim: In this study our aim was to measure cell characteristics that are critical for retention at the injury site after therapeutic delivery. Cells were cultured under conditions typical of current standard best practice. The impact of passage number was assessed and assays were performed in low oxygen (2%) as an in vitro model of physiologic oxygen tension at injury sites. The effect of chemokine preconditioning with SDF1 was also assessed.Materials & methods: Bone marrow mononuclear cells from patients recruited to the REGENERATE Phase II clinical trials, along with MSCs from healthy volunteers subjected to a short period of expansion, were assessed for attachment and migration ability. Using MSCs from healthy donors, the effect of reduced oxygen was also assessed.Results: Short-term expansion resulted in increased cell attachment but decreased rate of migration, whereas attachment and migration of patient-derived bone marrow mononuclear cells was highly heterogeneous. Reduced oxygen impaired MSC attachment but not migration. Finally, SDF1 did not improve any of the responses.Conclusion: The basic functional responses of MSCs required for retention and engraftment alter rapidly even over a relatively short expansion period. This needs careful consideration when expanding cells to achieve clinical quantities for therapy.